Pesakit Yang Tiada Harapan Hidup Menurut Perspektif Fiqh: (The Position of Terminal Ill Patient from Fiqh Perspectives) - Abdul Rahman, Noor Naemah; Rosele, Muhammad Ikhlas; Shaikh Mohd Salleh, Shaikh Mohd Saifuddeen; Ibrahim, Abdul Halim (Online Journal of Research in Islamic Studies, 2024)
The development of technology today has an impact on the social structure of society, especially those involving aspects of health, treatment, and end-of-life care. With the development of the latest technology such as the use of ventilators, Bi-Pap and C-Pap machines, blood pressure monitors, feeding tubes, beds and kidney machines and others have been able to guarantee that patients facing high-risk diseases will lose their lives (terminal ill), has gained new hope either from the point of healing or extending life span. However, there are patients who are in a position where there is no hope of life or more precisely called the level of medical futility. A series of issues arise from that that require a legal response. Among the issues is the position of stopping treatment for the patient, the party that has the right to make decisions on behalf of the patient when he is unable to make decisions, the rights of the patient and so on. Thus by using a qualitative approach by collecting library data. Then the data will be analyzed in a mixed methodology regarding the position of patients who have no hope of life and some selected issues.